One World, One Global Village - Trujillo Liñán, Laura (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
Through the COVID-19 pandemic, the world was involved in a series of changes that impacted aspects as important as education. Some digital platforms took this as an opportunity to evaluate and improve educational conditions around the world. This is the case of Coursera, which, through its data mining and online courses, showed the world the need to change the way education is taught to provide students with the necessary tools to work in today’s world.